Conceptual 3D design of batch distillation column by using AVEVA PDMS - Taufik, Abu Bakar (2013)
The main objective of this project is to design a 3D view of distillation column for biodiesel process using AVEVA PDMS. The design constraints specify that the biodiesel distillation column must be sized to fit into a standard truck-trailer. 3D design is a significant to solve the 2D design problem. The first step of this project is drawing process flow diagram (PFD) for biodiesel process.After that the simulation and sizing begin. Simulation is based on PFD and is done using ASPEN Plus. After that the resident time for distillation column can be obtained. Then the Process and Instrumentation Diagram (P&ID) will be drawn. All the control systems are included in the P&ID before 3D design. This is important to ensure the safety of equipment. After completion of P&ID, simulation process and the size of the reactor in the form of 3D can be done. All parameter involved before will be used in 3D design. 3D design is done by using AVEVA PDMS. As a result, by using AVEVA PDMS software the design will be more accurate. This software prove that the 3D design give more benefit compare to the 2D design. The end result is better product, size can be optimized and no faults in design for example equipment layout and pipe clashing. For recommendation the design structure must be including in the plant for example rack to support the equipment, the size of the trailer can also be changed and more safety precaution has to be taken in design.